2012
DOI: 10.1007/s10120-012-0225-7
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic submucosal dissection in the treatment of gastric submucosal tumors: results from a retrospective cohort study

Abstract: Background A submucosal tumor (SMT) of the stomach, which is an occasional finding during routine upper gastrointestinal endoscopy, may pose diagnostic and therapeutic challenges. Methods To assess whether endoscopic submucosal dissection (ESD) is a feasible approach to definitively cure SMTs, the authors performed a retrospective cohort study with two endoscopic italian centers.Results The study consisted of 20 patients with SMTs who underwent ESD. The patients underwent ESD and were followed up by endoscopy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 25 publications
0
33
1
2
Order By: Relevance
“…Thus, we assume that endoscopic approach should be highly selective. To our knowledge, our study contains the largest number of GIST in the UGIT resected by the endoscopic procedure, considering that previous studies only included small number of case series attached to clinical data of gastric SETs resected by ESD, STER or EFTR, [15][16][17][18][19][20][27][28][29][30] and their follow-up duration was relatively short, ranging from 2 to 21 months, 15,17,20,27,28,30,31 or even not presented. 16,18,29 Endoscopically resected cases in our study were followed up for 46 months on average, longer than previous studies, but nevertheless, the recurrence rate was 2.2%.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, we assume that endoscopic approach should be highly selective. To our knowledge, our study contains the largest number of GIST in the UGIT resected by the endoscopic procedure, considering that previous studies only included small number of case series attached to clinical data of gastric SETs resected by ESD, STER or EFTR, [15][16][17][18][19][20][27][28][29][30] and their follow-up duration was relatively short, ranging from 2 to 21 months, 15,17,20,27,28,30,31 or even not presented. 16,18,29 Endoscopically resected cases in our study were followed up for 46 months on average, longer than previous studies, but nevertheless, the recurrence rate was 2.2%.…”
Section: Discussionmentioning
confidence: 98%
“…We performed endoscopic resection as opposed to surgical resection to remove the tumor, due to the patient’s age (95 years). Several authors have described the usefulness of ESD for small and asymptomatic gastric submucosal tumors (16,17). It was recently reported that endoscopic resection of subepithelial tumors of the stomach has a high success rate with few adverse events (18).…”
Section: Discussionmentioning
confidence: 99%
“…An initial study by Li et al on 29 neuroendocrine tumors showed that 28 lesions (96.6%) in the upper GI tract could be completely resected, with only 1 case of delayed bleeding, 0 perforations, and 1 recurrence [9]. Several other case series have recently reported successful ESD for various gastric submucosal tumors such as ectopic pancreas, ectopic spleen, leiomyoma, and gastrointestinal stromal tumor (GIST) [23, 24]. In another case series from France, the authors reported successful resection of 33 submucosal lesions in the stomach for lesions <20 mm, with the majority of lesions being resected by ESD [25].…”
Section: Discussionmentioning
confidence: 99%